1998
DOI: 10.1099/0022-1317-79-4-831
|View full text |Cite
|
Sign up to set email alerts
|

Intradermal immunization with a bovine herpesvirus-1 DNA vaccine induces protective immunity in cattle.

Abstract: Although intramuscular (i.m.) injection of DNA encoding glycoprotein D (gD) of bovine herpesvirus-1 (BHV-1) induces immune responses in cattle, this route of delivery is inefficient. Here we assessed three parameters that may enhance the efficacy of a gD DNA vaccine in cattle. First, the immune response generated by i.m. injected plasmid expressing a secreted form of gD (tgD) was determined and found to be very similar in magnitude to the response induced by gD-expressing plasmid. Secondly, gD- and tgD-express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
0
1

Year Published

1999
1999
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(59 citation statements)
references
References 43 publications
5
53
0
1
Order By: Relevance
“…To our knowledge, this phenomenon had not been further explained or studied for other antigens of BoHV-1. Here, we first confirmed that the intradermal administration of a construct encoding secreted gD induced significantly higher IgG and virus neutralising titres in cattle than a construct encoding full-length gD but we failed to confirm that truncated gD also elicited enhanced cellular immunity [54]. Although the deletion of the transmembranous anchor of gC also induced secretion of the truncated protein, it had a slight adverse effect on both IgG and virus neutralising titres.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…To our knowledge, this phenomenon had not been further explained or studied for other antigens of BoHV-1. Here, we first confirmed that the intradermal administration of a construct encoding secreted gD induced significantly higher IgG and virus neutralising titres in cattle than a construct encoding full-length gD but we failed to confirm that truncated gD also elicited enhanced cellular immunity [54]. Although the deletion of the transmembranous anchor of gC also induced secretion of the truncated protein, it had a slight adverse effect on both IgG and virus neutralising titres.…”
Section: Discussionmentioning
confidence: 80%
“…In the present study, we describe the characterisation and the evaluation of several DNA vaccines in cattle in similar conditions. Although these DNA vaccines conferred an immune response comparable to that described by other groups [17,54], they induced weaker immune response and virological protection than the best protocol developed previously with conventional marker vaccine [20]. Therefore, a further experiment will aim at optimising some of the parameters known to modulate the efficacy of DNA vaccines such as the adjuvancy of immunostimulatory CpG motifs in the plasmid backbone [43].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations